2013
DOI: 10.20529/ijme.2013.029
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of clinical ethics among healthcare providers in a government hospital, Chennai

Abstract: The growing public concern about the ethical conduct of healthcare professionals highlights the need to incorporate clinical ethics in medical education. This study examined the knowledge and practice of clinical ethics among healthcare providers in a government hospital in Chennai. A sample of 51 treating physicians and 58 other non-physician service providers from the hospital answered a self-administered, semi-structured questionnaire on their knowledge of and adherence to ethical principles, and the proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 6 publications
(8 reference statements)
0
24
0
1
Order By: Relevance
“…7 However, modern medicine seeks to avoid a paternalistic (doctor knows best) approach to patients. Instead it considers the doctor and patient mutually engaging in the decision making with the final decision on treatment options being that of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, modern medicine seeks to avoid a paternalistic (doctor knows best) approach to patients. Instead it considers the doctor and patient mutually engaging in the decision making with the final decision on treatment options being that of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…It needs to be introduced in education curricula, and training on clinical ethics in health care settings is also beneficial. 72,73 Medical schools organize clinico-pathological conferences (CPC) where students and faculty interact with each other, but discussions on judgments related to health care or liability cases and ethics are not often presented. Interactive programs in medical schools and clinical practices about such issues will help students and physicians understand not only the intricacies of laws related to health care and the shortcomings of health professionals and health systems, but also strengthen their understanding of ethics and laws, improve their practice and standard of care, and minimize litigation issues.…”
Section: Education and Trainingmentioning
confidence: 99%
“…A stunning 75.7 % was of the opinion that knowledge of ethics was of little to no importance in their work (Janakiram and Gardens 2014). A study in a government hospital in Chennai among 51 treating physicians and 58 other non-physician service providers on knowledge and practice of clinical ethics found that these medical professionals needed more ethics education (Subramanian et al 2013). These were two small-scale studies, and the results cannot necessarily be projected to all Indian postgraduate medical students or medical professionals.…”
Section: Healthcare Ethics In Medical Education In Indiamentioning
confidence: 99%